AGRICULTURAL PROTECTIONISM OF THE EUROPEAN UNION IN THE CONDITIONS OF INTERNATIONAL TRADE LIBERALIZATION - Marković, Ivan; Marković, Milan (Economics of Agriculture, 2014)
The key objective of agricultural protectionism is reflected in the protection and developing of agriculture sector. Integrated parts of this policy in the European Union are the initial model of agricultural protectionism and a new strategy of agricultural policy, which emerged as a response to the shortcomings of previously existing model. The paper presents the key reforms of agricultural policy, conditioned to internal problems and pressures in the negotiations of trade liberalization of agricultural and food products. Reform solutions for the period of 2014 to the 2020 will have similar goals. The priority will be to develop sustainable food production and sustainable management of natural resources. There is a widespread awareness of sustainable development that includes not only the economic component (which is reflected in the increase in productivity and production efficiency), but also an environmental component (the need to preserve the environment), as well as the social component of sustainable development (integrated rural development). Conducting negotiations in the framework of liberalization of agricultural and food products, there was a gradual reduction of restrictive measures in the field of domestic agriculture protection. However, the European food market is still highly protected from foreign competition because of the many features of the agricultural production sector and the importance of agriculture for the entire society. It is certain that the CAP will lose its narrow agricultural character.